Recentring the necropolitics of covid-19: A perspective from Angola - Blanes, Ruy Llera (State-society relations around the world through the lens of the covid-19 pandemic: Rapid test, 2023)
In this chapter, I approach the debates on the biopolitics of COVID-19 from a de-centred, Global South perspective. I analyse the particular trajectory of COVID-19 in Angola, a country with a history of authoritarian governance and haphazard health administration characterised by multiple endemic and epidemic episodes of outbreaks. On the basis of years of ethnographic research in Angola, including during the pandemic, I explore the different figures, landmarks, debates and episodes of conflict that have marked the trajectory of COVID-19 in Angola - in particular, that which concerns the political governance of COVID-19. Conceptually, I will explore both continuities and ruptures presented by COVID-19 when it comes to social and political inequalities, and engage in recent discussions about the ŉecropolitics of COVID-19' which enable a re-reading of Achille Mbembe’s classic formulation of postcolonial rule in Africa. © 2024 selection and editorial matter, Federica Duca and Sarah Meny-Gibert; individual chapters, the contributors.